2018
DOI: 10.1364/oe.26.005616
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-selective mid-infrared metamaterial absorbers with multiple tungsten cross resonators

Abstract: Wavelength-selective metamaterial absorbers in the mid-infrared range are demonstrated by using multiple tungsten cross resonators. By adjusting the geometrical parameters of cross resonators in single-sized unit cells, near-perfect absorption with single absorption peak tunable from 3.5 µm to 5.5 µm is realized. The combination of two, three, or four cross resonators of different sizes in one unit cell enables broadband near-perfect absorption at mid-infrared range. The obtained absorption spectra exhibit omn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 68 publications
(101 reference statements)
0
31
0
Order By: Relevance
“…Furthermore, based on the equivalent RLC circuit model of the MIM three-layer structure, the input impedance of the MA is dependent on the intrinsic properties of both materials (metal and dielectric) and resonator shapes [2], [31], [38]. By tailoring the above parameters, the impedance matching band can be controlled, thus the tunable absorption band of the MA can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, based on the equivalent RLC circuit model of the MIM three-layer structure, the input impedance of the MA is dependent on the intrinsic properties of both materials (metal and dielectric) and resonator shapes [2], [31], [38]. By tailoring the above parameters, the impedance matching band can be controlled, thus the tunable absorption band of the MA can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1 a, ultrabroadband absorption can be realized at wavelengths ranging from 380.0 to 2137.5 nm with absorptivity higher than 90% and average absorption of A av = 96.4%. The RAB of the Cr-based MA is 139.6%, which is larger than many types of MAs such as MIM-based MAs [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], multi-sized MAs [ 21 , 22 , 23 , 24 , 25 , 26 ], and HMM-based MAs [ 42 , 43 , 44 , 45 , 46 ]. In addition, although only three metal/dielectric stacks are required, the RAB of the Cr-based MA is also comparable with those of the MAs such as multilayered-based nanocones [ 47 ] and pyramids [ 48 , 49 ].…”
Section: Design and Characterization Of The Proposed Mamentioning
confidence: 99%
“…To extend the bandwidth, multi-sized resonators with patterns such as strips [ 21 , 22 ], patches [ 23 , 24 ], ellipses [ 25 ], and crosses [ 26 ] can be integrated together to form a supercell, and the absorption bandwidth of the multi-sized MA can be effectively improved due to the blending of multiple resonant frequencies. Unfortunately, the achievable bandwidth is limited because the number of possible integrated resonators in a supercell is restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Since Landy et al demonstrated the first metamaterial absorber with one perfect absorption peak in the microwave band through an experiment 19 , the control and engineering of the spectral absorption properties of MPAs has attracted significant interest. In their experiment, broadband perfect absorption was achieved with MPAs in microwave regime [20][21][22][23][24] and was extended from visible [25][26][27][28][29][30][31][32][33][34][35][36][37] , infrared [38][39][40][41][42][43][44][45][46][47][48][49][50][51] and THz [52][53][54][55][56][57] bands. This study will compare these representative theoretical and experimental works on the topic of broadband MPAs from visible to infrared bands in supplement document.…”
Section: Introductionmentioning
confidence: 98%
“…This study will compare these representative theoretical and experimental works on the topic of broadband MPAs from visible to infrared bands in supplement document. Research on broadband absorbers has led to the creation of a number of methods which are successfully used for expanding the absorption band using laminated structures 33,36,41 , coupling multi-sized metallic resonators 40,42,45,50 and inlaying metallic structures in the dielectric layer 25,27,29,31,49 . The common absorption mechanism of these traditional methods is coupling multiple resonances of broad wavelength bandwidth excited by multi-sized metallic resonators in the structures.…”
Section: Introductionmentioning
confidence: 99%